PENGARUH GADGET TERHADAP MOTIVASI BELAJAR SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI 1 SIAU BARAT SELATAN - Oktavianus Katiandagho, Anggris (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2023)
The use of gadgets among students of SMP Negeri 1 Siau Barat Selatan is a witness to change in student learning behavior and technological advances. This research aims to explore this, focusing on the negative impact of gadget use on students' learning motivation. This research identifies gadget usage patterns, analyzes their impact on learning motivation, and presents recommendations for more effective management in educational environments. The research method used was quantitative, involving students from South West Siau 1 Middle School as samples. The research results show that gadget use tends to be intense, involving many students in various activities. Data analysis shows a negative relationship between the intensity of gadget use and student learning motivation. Factors such as distraction, dependence on social media, and lack of time management are the main causes of low learning motivation. The rationale for this research was built by referring to the theory of learning motivation, the theory of the use of technology in education, and the theory of adolescent development. The proposed hypothesis strengthens the finding that the intensity of gadget use is negatively correlated with the level of student learning motivation. This research contributes to an in-depth understanding and treatment of the impact of gadget use in educational contexts. It is hoped that the findings of this research can guide educational institutions, parents, students, and future researchers in managing the use of gadgets so that they do not hinder students' learning motivation.